Penyelesaian Sengketa Konsumen Oleh Badan Penyelesaian Sengketa Konsumen (BPSK) - Riris Nisantika; Ni Luh Putu Egi Santika Maharani (Jurnal Locus Delicti, 2021)
Taxes are compulsory contributions to the state that are owed by individuals or entities that are compelling based on law, without receiving direct compensation and used for the state’s needs for the greatest prosperity of the people. Tax payments are used to finance state households so that the benefits are felt by the wider community or for the public interest. The film industry is a creative industry engaged in the media, arts and culture. Compared to other creative industry sectors, the film, video and photography industries have the highest creativity and knowledge capital, as forms of intangible assets. Effectiveness means that the goals that have been planned before can be achieved or in other words, the targets are achieved because of the activity process. With the existence of an open letter and protests by the film industry, it has resulted in the provision of relief and incentives from the finance minister for entertainment tax, especially for films. The purpose of this study is to determine the arrangements regarding consumer dispute resolution and dispute resolution mechanisms in the Consumer Sengkera Settlement Agency. The research method used is the normative research method. The legal materials used are primary and secondary legal materials and the data analysis technique uses qualitative methods. The results of his research are (1) the settlement of disputes in consumer protection is regulated in Law no. 8 of 1999 concerning Consumer Protection which regulates dispute resolution is divided into 2 (two), namely court channels and outside court channels such as negotiation, conciliation, mediation, and others. BPSK as a dispute resolution agency domiciled in the provincial capital, and (2) consumer dispute resolution at BPSK, in Article 15 Paragraph (1) of the Republic of Indonesia's Minister of Industry and Trade Decree No. 350 / MPP / Kep / 12/2001 regarding the implementation of the duties and authorities of BPSK stated that consumers or business actors who feel their rights have been impaired can submit a consumer dispute resolution request to.